A phase I/II trial of 5-fraction stereotactic radiosurgery with 5-mm margins with concurrent temozolomide in newly diagnosed glioblastoma: primary outcomes. Issue 8 (31st January 2020) - Azoulay, Melissa; Chang, Steven D; Gibbs, Iris C; Hancock, Steven L; Pollom, Erqi L; Harsh, Griffith R; Adler, John R; Harraher, Ciara; Li, Gordon; Hayden Gephart, Melanie; Nagpal, Seema; Thomas, Reena P; et al.
Abstract: Background: We sought to determine the maximum tolerated dose (MTD) of 5-fraction stereotactic radiosurgery (SRS) with 5-mm margins delivered with concurrent temozolomide in newly diagnosed glioblastoma (GBM). Methods: We enrolled adult patients with newly diagnosed glioblastoma to 5 days of SRS in a 3 + 3 design on 4 escalating dose levels: 25, 30, 35, and 40 Gy. Dose limiting toxicity (DLT) was defined as Common Terminology Criteria for Adverse Events grades 3–5 acute or late CNS toxicity, including adverse radiation effect (ARE), the imaging correlate of radiation necrosis. Results: From 2010 to 2015, thirty patients were enrolled. The median age was 66 years (range, 51–86 y). The median target volume was 60 cm 3 (range, 14.7–137.3 cm 3 ). DLT occurred in 2 patients: one for posttreatment cerebral edema and progressive disease at 3 weeks (grade 4, dose 40 Gy); another patient died 1.5 weeks following SRS from postoperative complications (grade 5, dose 40 Gy). Late grades 1–2 ARE occurred in 8 patients at a median of 7.6 months (range 3.2–12.6 mo). No grades 3–5 ARE occurred. With a median follow-up of 13.8 months (range 1.7–64.4 mo), the median survival times were: progression-free survival, 8.2 months (95% CI: 4.6–10.5); overall survival, 14.8 months (95% CI: 10.9–19.9); O 6 -methylguanine-DNA methyltransferase hypermethylated, 19.9 months (95% CI: 10.5–33.5) versus 11.3 months (95% CI: 8.9–17.6) for no/unknown hypermethylation ( P = 0.03), and 27.2 months (95% CI: 11.2–48.3) if late ARE occurred versus 11.7 months (95% CI: 8.9–17.6) for no ARE ( P = 0.08). Conclusions: The per-protocol MTD of 5-fraction SRS with 5-mm margins with concurrent temozolomide was 40 Gy in 5 fractions. ARE was limited to grades 1–2 and did not statistically impact survival.